Critical Reflections on the Effective Implementation of ICTs in Moroccan Universities - Hicham Laabidi (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2017)
Computers offer several opportunities that encourage the promotion of teaching and learning experiences.  Like many other nations, Morocco has understood the importance of using computers in schools and universities. For this reason, the Moroccan government has launched several projects aiming at the diffusion of Information and Communication Technologies (ICTs) in education system. Actually, ICTs are useful for both teachers and students in the sense that they help teachers develop professionally. Also, students can increase their achievements and become independent learners. This paper aims to examine the various factors that have high impact on English professors’ use of computer technologies for pedagogical purposes in Moroccan universities. Descriptive analysis of means, and standard deviations were used to analyse the collected data. Also, inferential statistics, mainly Pearson Product Moment Correlation, were employed to account for this correlation. The findings revealed that lack of institutional support has a big influence on professors’ decision to utilize or refrain from using ICTs in their classroom practices.